Effect of Limonene on Cancer Development in Rodent Models: A Systematic Review - Zhou, Jingyi; Azrad, Maria; Kong, Lingyan (Frontiers in Sustainable Food Systems, 2021)
Cancer is a major health issue and one of the leading causes of death worldwide. Many natural compounds, e.g., lycopene, curcumin, resveratrol, etc., have been shown to inhibit the growth of cancer cells. Similarly, limonene, a major active component in citrus essential oils and widely used flavoring additive, has demonstrated anticarcinogenic effects in both cell and animal studies. This systematic review aimed to evaluate the anticarcinogenic effects of limonene and its potential underlying mechanisms. Eight peer-reviewed articles published in English between 2000 and 2020 were identified after screening using MEDLINE, Academic Search Premier, and CINAHL plus. All 8 studies showed an effect of limonene on reducing tumor burden, resulting in either decreased size, number, weight, or multiplicities of tumors. Limonene treatment extended the latency and survival periods in 2 studies yet did not reduce tumor incidence rate in another study. Limonene was shown to promote cell apoptosis in 4 studies that examined either the apoptosis index or apoptosis related gene/protein expressions. Two studies tried to explain the cancer preventive mechanisms of limonene and found limonene could restore the antioxidant capacity or immune functions that were impaired by cancer. These results supported the potential applicability of limonene on inhibiting cancer development, yet the real-world applicability on human requires more research and evaluation through clinical studies. Systematic Review Registration: PROSPERO, identifier: CRD42020168387.